Strategy of Creative Economy Development on Small Micro Enterprises and Medium (SMEs) in Medan City - Handayani, Leni; Masitah, Tina Herianty; Rukmini, Rukmini; Murniyanti, Sri; Azahra, Nova (Westscience Press, 2024)
This study shows how the implications of the strengthening strategy and recommendations for the SMEs development policy strategy in Medan City. This study is very important in the context of developing SMEs as creative economic activists in the future. This study uses a quantitative descriptive method. In general, qualitative research is not patterned with a design format consisting of three models, namely descriptive format, verification format, and grounded research format. The subjects of the study were 120 respondents of SMEs actors registered with the Medan City Cooperative and SMEs Service, which became the object of the study, namely about SMEs empowerment through strengthening the creative economy to accelerate poverty alleviation in Medan City. The sampling technique used was purposive sample with data collection using questionnaires. The results of the study stated that the development of creative economic handicrafts in Medan City was carried out by optimizing human resources through skills development and training. The right approach and strategy in developing handicraft innovation is with 5P (enabling, strengthening, protection, support, and maintenance). Because this strategy can cover all lines of the creative economy in handicrafts in order to increase local economic potential. The strategy for developing handicraft businesses in Medan City uses the SO strategy, where this strategy is used to utilize existing strengths and opportunities to minimize weaknesses and threats by relying on product advantages and expanding market networks outside the Medan City area. The novelty in this study is that this study is more comprehensive (comprehensive) in examining the acceleration of poverty alleviation in Medan City with the right strategy in increasing the selling value of SMEs products.